Large-Scale and High-Density pMUT Array Based on Isolated Sol-Gel PZT Membranes for Fingerprint Imaging. Issue 7 (17th May 2017) - Chen, Yuan-Quan; Li, Yu-Xing; Chen, Yan; Ju, Zhen-Yi; Tao, Lu-Qi; Pang, Yu; Yang, Yi; Ren, Tian-ling
Abstract : In this work, we proposed a novel ultrasonic transducer array based on an array of 50 × 50 piezoelectric micromachined ultrasonic transducers (pMUTs). The structure was specially designed for fingerprint imaging application. The pMUTs array were fabricated with isolated piezoelectric lead zirconate titanate (PZT) cells to reduce the crosstalk between adjacent units, and released by deep-silicon etching from the back side. The cell size and pitch of pMUTs were 50 μm and 100 μm, respectively. Layer-by-layer annealing method was used instead of one-time annealing during the fabrication of sol-gel based PZT film. The resonance frequency of the pMUT was about 24.82 MHz which agreed well with simulated 25.02 MHz. Besides, the effective electro-mechanical coupling coefficient (keff ) and mechanical quality factor (Q factor) of the transducer were 0.1293 and 198, respectively. The equivalent circuit of the transducer was established and analyzed. The fitted admittance circle agreed well with the experimental result. This demonstration of pMUTs array has profound potential for large-scale, high-density, and high-frequency fingerprint imaging.